ANALISA DAN PERANCANGAN APLIKASI REKAM JEJAK KOMPETENSI DAN PENUGASAN INSPEKTUR MIGAS SEBAGAI LANGKAH AWAL PEMBENTUKAN DATABASE KEMAMPUAN PERSONAL PJIT MIGAS - Erzed, Nixon (Lembaga Penerbitan Universitas Esa Unggul, 2018)
To ensure the protection of labor safety and environmental protection in the upstream oil and gas industry, it requires routine technical inspection of oil and gas equipment and installations. The quality of the results of technical inspections is highly dependent on the competence and experience of the inspector (inspector expert) assigned. In this research an application of competency track record and assignment of each oil and gas inspector registered in the Directorate General of Oil and Gas, Ministry of Energy and Mineral Resources (ESDM) is assigned. This system will register the registered oil and gas inspector, complete with bio-data and certification of expertise owned in a parent data. Referring to the master inspector's data, the inspector's assignment activity will be recorded by a technical inspection service company (PJIT) that oversees the inspector. The database that is built at a later stage can be used to avoid the registration of an inspector by more than one PJIT. This system will utilize information technology and global networks, so that the PJIT capability database system can be accessed from anywhere, which can facilitate the input process and information appearanceÃ‚Â Keywords: PJIT inspector, competence, assignment.